PUSAT PELAYANAN AUTIS DI BANJARBARU - Agoes, Alya Anisah Savitry; Mentayani, Ira (UNIVERSITAS LAMBUNG MANGKURAT, 2021)
Autism is not a disease, but rather a spectrum disorder in the brain that causes autistic people cannot be completely cured. The best thing that can be done is to provide appropriate care to help people with autism adjust to their conditions, both therapeutically and educatively. Adequate facilities are urgently needed to develop and explore the potential that exists in every autistic person. The service facilities available at this time are still not good enough in terms of safety and comfort, and have not been able to meet the needs of people with autism to support their personal development activities. So that it is felt necessary to have a special Care Center for people with autism who are able to be a good and appropriate means of therapy and learning for people with autism to develop their abilities. This was realized by using the Human Centered Design (HCD) method and the concept of applying the principles of The Autism ASPECTSS Design Index to create a good and appropriate Autism Care Center, and in accordance with the characteristics and needs of people with autism.